153. The Effect of Timing of Tetanus–Diphtheria and Pertussis Vaccine Administration in Pregnancy on The Avidity of Pertussis Antibodies. (26th November 2018) - Raya, Bahaa Abu; Giles, Michelle; Kollmann, Tobias; Sadarangani, Manish
Abstract: Background: Tetanus–diphtheria–pertussis (Tdap) vaccination in pregnancy is currently recommended in many countries. The optimal timing of pertussis immunization in pregnancy is not well established, leading to different recommendations. We aimed to determine the effect of timing of vaccination with Tdap in pregnancy on the umbilical cord avidity of antipertussis toxin (PT) immunoglobulin G (IgG). Methods: Avidity of anti-PTIgG was assessed using ammonium thiocyanate (NH4 SCN) at concentrations between 0.25 M (to measure low avidity antibodies) and 3 M (to measure high avidity antibodies). Anti-PT IgG levels achieved at each NH4 SCN concentration were calculated. T -tests were used to compare anti-PT IgG levels between newborns of women vaccinated in early (28–32 weeks gestation) and late (33–36 weeks gestation) third trimester. Pearson correlation assessed the relationship between the timing of vaccination and anti-PT IgG levels. Results: Newborns of women vaccinated with Tdap in early third trimester ( n = 43) had higher anti-PT IgG levels at 1 M and 2 M NH4 SCN concentrations compared with newborns of women vaccinated in late third trimester ( n = 47), 2.4 international units (IU)/mL vs. 1.9 IU/mL ( P = 0.0073) and 2.3 IU/mL vs. 1.7 IU/mL ( P = 0.0354), respectively, after adjustment for gestational age at birth. There was a negative association between later timing of vaccination in third trimester and anti-PT IgG levels achieved at 0.5 M, 1 M, 1.5 M, and 2 M NH4 SCN (all P ≤ 0.02). There was a positive association between increasing time between vaccination and delivery and anti-PT IgG levels achieved at 0.5 M, 1 M, 1.5 M, and 2 M NH4 SCN (all P ≤ 0.02). Conclusion: Vaccination against pertussis during early third trimester results in higher levels of high avidity antibodies compared with vaccination in late third trimester. High avidity antibodies may confer greater protection to the neonate supporting recommendations for vaccination at 28–32 WG vs. 33–36 WG. Disclosures: All authors: No reported disclosures.